The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1111/j.1476-5381.1984.tb10105.x
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between hexamethonium and tubocurarine on the rat neuromuscular junction

Abstract: 1 The ability of hexamethonium (C6) to reverse the neuromuscular blocking action of tubocurarine (Tc) has been reinvestigated at the voltage clamped endplate of the omohyoid muscle of rat. The possibility that a weak anticholinesterase action of C6 could contribute to the paradoxical potentiation of the peak amplitude of the endplate response has been examined. 5 When tested against responses to short ionophoretic pulses of agonists, C6 was less effective against ACh ((EC5o ca. 300 JiM) than against carbachol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
5
24
0
Order By: Relevance
“…Of the drugs used in this study, tubocurarine, pancuronium and hexamethonium have all been shown to be capable ofblocking the receptor-activated ion channel at the frog neuromuscular junction, although in the cases of tubocurarine and pancuronium, only at concentrations around 10 times higher than were used in this study (Lambert et al, 1983 for review). In addition, Rang & Rylett (1984) have observed that hexamethonium blocks the acetylcholine-receptor (AChR)-activated ion channel in the rat omohyoid muscle at concentrations greater than Tubo: (n = 8) Hex: (n = 6) Atra: (n = 6) Ebtx: (n = 5) 0.4 mM. Thus, this mechanism could account for tetanic fade produced by the millimolar concentrations of hexamethonium used in this study.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Of the drugs used in this study, tubocurarine, pancuronium and hexamethonium have all been shown to be capable ofblocking the receptor-activated ion channel at the frog neuromuscular junction, although in the cases of tubocurarine and pancuronium, only at concentrations around 10 times higher than were used in this study (Lambert et al, 1983 for review). In addition, Rang & Rylett (1984) have observed that hexamethonium blocks the acetylcholine-receptor (AChR)-activated ion channel in the rat omohyoid muscle at concentrations greater than Tubo: (n = 8) Hex: (n = 6) Atra: (n = 6) Ebtx: (n = 5) 0.4 mM. Thus, this mechanism could account for tetanic fade produced by the millimolar concentrations of hexamethonium used in this study.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, this mechanism could account for tetanic fade produced by the millimolar concentrations of hexamethonium used in this study. Rang & Rylett (1984) also demonstrated that hexamethonium produced AChR block and inhibition of acetylcholinesterase. Cholinesterase inhibition would be expected to increase fade produced by a use-dependent mechanism such as ion channel block, yet fade due to hexamethonium was partially reversed by neostigmine.…”
Section: Discussionmentioning
confidence: 99%
“…At both types of junctions the blockade increased as the membrane potential was hyperpolarized. To test whether an anticholinesterase action of hexamethonium (Gandiha, Green & Marshall, 1972;Rang & Rylett, 1984) might contribute to the observed difference in its potency at the two types of junctions AChE activity at normal end-plates was blocked by addition of 3 ,sM-neostigmine and depression of end-plate currents (e.p.c.s) by 200 sM-hexamethonium was re-examined. Nerve-evoked e.p.c.s were depressed to 81 + 1 % (S.E.…”
Section: Resultsmentioning
confidence: 99%
“…Various mechanisms have been put forward to explain this phenomenon. Some authors are of the opinion that hexamethonium-induced fade is a consequence of the attenuation of the positive feedback process involved in the acetylcholine release at the prejunctional membrane of the junction (Bowman,1980;Gibb and Marshall, 1984;Miguel et al,2003) rather than a use dependent block of the open ion channel (Diane and Humphrey,1988;Gibb and Marshall,1986;Richard andJohn,1981,Rang andRylett, 1984) in the post junctional membrane. Some other authors however argue that end plate potential rundown or tetanic fade reflects a complex (pre and postsynaptic) set of phenomena that may also depend on species and stimulating conditions.…”
Section: Discussionmentioning
confidence: 99%